Complications of Bilateral Sagittal Split Osteotomy in Patients with Mandibular Prognathism - Majid Eshghpour; Baratolah Shaban; Reza Shahakbari; Reza Mahvelati Shamsabadi; Amir Hossein Nejat (Mashhad University of Medical Sciences, 2013)
Introduction: Bilateral sagittal split osteotomy (BSSO) of mandible is vastly used in treatment of mandibular deficiencies and discrepancies. Since this method could affect esthetic as well as function, evaluating these effects from various aspects is crucial. This study assessed the effects of this technique on the function of masseter muscle, jaw movements, and sensory changes along with failures in screws used for fixation. Methods: 48 patients with mandibular prognathism participated. Electromyography (EMG) of the masseter muscle; limits of jaw movements including maximum opening (MIO), protrusive (PM), lateral movements (LLE and LRE); presences of sensory changes and two point discrimination test; and number of removed screws were recorded at the baseline, 3 months, and 6 months after surgery. Results: EMG activity of masseter decreased significantly 3 months after the surgery. However, after 6 months the masseter activity revealed no statistically significant difference with baseline activity. There was a significant decrease in MIO and PM after 3 months. The 6 month measurement of MIO and PM was also lower than baseline. However, no difference was observed between LRE and LLE in both follow up sessions. Among 46 patients, 27 patients developed lip paresthesia 3 months after surgery. After 6 month, lip paresthesia remained in 11 patients. Among 276 screws used for fixation 3 screws removed due to exposure to oral cavity and 2 due to patient discomfort. Conclusion: As BSSO in patients with mandibular prognathism revealed temporary functional and sensory changes, it is a safe and appropriate method in orthognathic surgery.